2017
DOI: 10.1038/nplants.2016.223
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of two jute species and insight into fibre biogenesis

Abstract: Jute (Corchorus sp.) is one of the most important sources of natural fibre, covering ∼80% of global bast fibre production1. Only Corchorus olitorius and Corchorus capsularis are commercially cultivated, though there are more than 100 Corchorus species2 in the Malvaceae family. Here we describe high-quality draft genomes of these two species and their comparisons at the functional genomics level to support tailor-designed breeding. The assemblies cover 91.6% and 82.2% of the estimated genome sizes for C. olitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 35 publications
4
77
1
Order By: Relevance
“…The stem of fibre crops is therefore ideal to carry out high throughput molecular analyses focusing on the cell wall, because its tissue polarity and spatial lignification gradient enable the study of sequential developmental stages. Several studies have indeed been published on fibre crops, namely flax 13, 14 , jute 1517 , ramie 18 , kenaf 19 , hemp 20, 21 where a molecular approach was adopted to shed light on the mechanisms underlying bast fibre differentiation and development. These studies have identified important genes involved in bast fibre development, notably chitinases and cellulose synthases 13 , as well as transcription factors 15, 16 and genes involved in secondary metabolism and monolignol-associated pathway 15, 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stem of fibre crops is therefore ideal to carry out high throughput molecular analyses focusing on the cell wall, because its tissue polarity and spatial lignification gradient enable the study of sequential developmental stages. Several studies have indeed been published on fibre crops, namely flax 13, 14 , jute 1517 , ramie 18 , kenaf 19 , hemp 20, 21 where a molecular approach was adopted to shed light on the mechanisms underlying bast fibre differentiation and development. These studies have identified important genes involved in bast fibre development, notably chitinases and cellulose synthases 13 , as well as transcription factors 15, 16 and genes involved in secondary metabolism and monolignol-associated pathway 15, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a very recent molecular study on flax, has shed light on the molecular mechanisms underlying advanced phases of bast fibre development, by identifying several transcription factors, as well as glycosyltransferases and unknown/not fully annotated genes 14 . Another recent study using transcriptomics/genomics has compared two varieties of jute differing in the cellulose/lignin fibre content and has demonstrated the expansion of lignin-biosynthetic genes with respect to flax 17 .…”
Section: Introductionmentioning
confidence: 99%
“…JRO-524, was primarily used to transfer premature flowering resistance (in early sowing) to indigenous types [18]. Thus an in-depth comparison of the present sequence with the recently published draft genome [3], would provide new insights that could help understand the mechanisms underlying premature flowering vis-à-vis photoperiodic control of bast fibre development in jute. This would allow breeding of high-yielding varieties with durable premature flowering resistance, which has been recently observed to be breaking down when dark jute crops are sown early under long-day conditions, possibly due to climate change.…”
Section: Resultsmentioning
confidence: 99%
“…Using a restriction site-associated DNA (RAD)-SNP linkage map, we have shown earlier that C. olitorius has the maximum syntenic relationship with cocoa followed by diploid cotton [12]. Recently, Islam et al [3] have also reported the same pattern of syntenic relationship for C. olitorius . In the present study, 501 (99.6%) of the published RAD-SNP markers were mapped to 288 contigs (8.53 Mbp) of the draft genome (Table 2).…”
Section: Data Descriptionmentioning
confidence: 97%
See 1 more Smart Citation